2021
DOI: 10.12669/pjms.37.4.4066
|View full text |Cite
|
Sign up to set email alerts
|

Observation on the Clinical Effect of Apatinib Combined with Chemotherapy in the Treatment of Advanced Non-Small Cell Lung Cancer

Abstract: Objectives: To evaluate the clinical effect of apatinib combined with chemotherapy in the treatment of advanced non-small cell lung cancer (NSCLC). Methods: Eighty patients with advanced NSCLC treated in Hebei General Hospital from January 2017 to July 2020 were randomly divided into two groups: the experimental group and the control group, each with 40 cases. Patients in the control group were treated with conventional paclitaxel combined with cisplatin chemotherapy, while patients in the experimental g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…However, they have toxic side effects and optimising their clinical applications requires the addition of other drugs to reduce these adverse effects. 11 , 12 The present study found an ORR in OS patients treated with the AP regimen of 31.25%, which is consistent with the results of previous studies. 13 , 14 …”
Section: Discussionsupporting
confidence: 93%
“…However, they have toxic side effects and optimising their clinical applications requires the addition of other drugs to reduce these adverse effects. 11 , 12 The present study found an ORR in OS patients treated with the AP regimen of 31.25%, which is consistent with the results of previous studies. 13 , 14 …”
Section: Discussionsupporting
confidence: 93%
“…It is one of the important causes of tooth loss, as shown in Figure 1 . The third national oral health epidemic survey shows that 80%~97% of adults in China have periodontal problems, and the degree and prevalence of lesions are much higher than those in developed countries [ 1 ]. China has gradually entered an aging society, and periodontitis has become the focus of attention.…”
Section: Introductionmentioning
confidence: 99%
“…There were 2 literature that could not obtain the full text. Finally, a total of 25 studies [5–29] were analyzed involving 2023 participants. Literature screening process and results are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eshuyou injection 20 mL + C Chemotherapy / ①④⑤ Cui et al 2011 [24] 22/20 Yang et al 2020 [28] 50/50 C:54.2 ± 4.5 T:55.1 ± 4.2…”
Section: Exclusion Criteriamentioning
confidence: 99%